Self‐inflicted stab wound at first thoracic vertebra - Masaya Ushio (Clinical Case Reports, 2022)
Abstract The patient was a 64‐year‐old woman who stabbed her neck with a kitchen knife in an attempt to commit suicide. The tip of the knife was chipped and lodged into the first thoracic vertebra. It was removed using a drill.